PENGARUH KAPASITAS SUMBER DAYA MANUSIA DAN KOMITMEN ORGANISASI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) KOTA MANADO - Manimpurung, Rivaldy; Kalangi, Lintje; Gerungai, Natalia (Universitas Sam Ratulangi, 2018)
The quality of government financial reporting is a normative prerequisite for the preparation of financial statements so that the resulting accounting information can be beneficial to users of financial statements. This is the aim of recognizing the effect of human resources and organizational commitment toward the quality of regional financial reports in BPKAD in Manado. The data collected through questionnaire distributions to 64 respondents were financial managers at BPKAD in Manado City. The data were analyzed using multiple linear regression analysis method with SPSS 17 program. The results showed that SDM Capacity has no positive effect on LKPD Quality and Organization Commitment positively and significantly affect the quality of Local Government Financial Reporting at BPKAD in Manado City.Keywords: Human Resource Capacity, Organizational Commitment, Quality of Financial Statement.